2015
DOI: 10.1111/exd.12883
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil localization to the basement membrane zone is autoantibody‐ and complement‐dependent in a human cryosection model of bullous pemphigoid

Abstract: Bullous pemphigoid (BP) is an autoimmune blistering disease characterized by antibodies (IgG and IgE) targeting cell-substrate adhesion proteins. A variety of BP models suggest that autoantibody-dependent neutrophil degranulation is essential for blister formation. However, lesional biopsies reveal a predominance of eosinophils and few neutrophils. Our goal was to evaluate the role of antibodies and complement in eosinophil localization, degranulation, and split formation at the dermo-epidermal junction (DEJ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…In agreement with a recent study, we observed that eosinophils activated solely with BP antibodies were not able to induce DES . Noteworthy, also similar to our study, IL‐5‐activated eosinophils have previously been demonstrated to bind throughout the dermis and not specifically to the basement membrane .…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a recent study, we observed that eosinophils activated solely with BP antibodies were not able to induce DES . Noteworthy, also similar to our study, IL‐5‐activated eosinophils have previously been demonstrated to bind throughout the dermis and not specifically to the basement membrane .…”
Section: Discussionsupporting
confidence: 93%
“…Eosinophilic cells derived from a human myeloid leukaemia cell line were shown to localize at the dermal‐epidermal junction in the presence of BP serum, but not upon incubation with control serum . The attachment to the DEJ was mediated by IgG and complement, whereas IgE had no effect . However, under these conditions, a subepithelial blistering could not be observed, presumably owing to a lack of eosinophil degranulation .…”
Section: Eosinophil‐induced Des In a Cryosection Modelmentioning
confidence: 93%
“…Eosinophilic cells derived from a human myeloid leukaemia cell line were shown to localize at the dermal‐epidermal junction in the presence of BP serum, but not upon incubation with control serum . The attachment to the DEJ was mediated by IgG and complement, whereas IgE had no effect .…”
Section: Eosinophil‐induced Des In a Cryosection Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…In this line, BP is clinically characterized by the presence of tense blisters along with intense pruritus, occurring preferentially on inflammatory, erythematous plaques. The use of mouse models allowed the demonstration that binding of autoantibodies onto their antigenic proteins is associated with an inflammatory cascade, including mast cell degranulation, and the recruitment and activation of neutrophils leading to dermal-epidermal separation 1,[11][12][13] . However, the role of eosinophils, which are the main tissue-infiltrated inflammatory cell type in the lesional skin of BP patient 14 , and especially how their granule proteins could impact BP disease severity and outcome still remains unclear in human.…”
mentioning
confidence: 99%